Colonization and production modes in Northeastern Atlantic Forest from the perspective of historical materialism - Barreto, Cristiane Gomes; Cezar, Kilma Gonçalves (Revista Econômica do Nordeste, 2016)
The process of colonization in the Northeast Atlantic Forest (NAF) has generated the most serious consequences for the conservation of its natural heritage. In order to generate data for the definition of policies and guidelines for management and conservation of forest remnants in NAF, the article seeks to elucidate the effects of production modes and colonization process on the man-nature relationship. Therefore, it tries to explain the relationships and motivations of the social structure and commercial of the colony in the NAF, based on a combination of elements of capitalism, feudalism and slavery, from the historical materialism point of view.